Waste paper recycling and the structure of forest industry - Pentti Forsman; Pertti Haaparanta; Tarja Heinonen (Bank of Finland, 1993)
The increasing use of recycled fibres in paper production may have large effects on the forest industry and on the structure of aggregate production. One of the most surprising results was reached is that in a Nordic type of economy where forestry is important, recycling requirements may cause an expansion in the forestry sector. This is certainly the case if capital is not mobile internationally and in this case we may observe even an expansion of paper production; otherwise the production of all types of pulp expands. This may hold also when capital is mobile internationally. ln this case paper production ceases but production of pulp based on recycled paper may increase. As the latter case seems to be closer to the situation prevailing in Europe, we expect recycling to create a structural change in the Nordic forest industry. This shift from refined paper products towards the production of pulp would be a turnaround in particular in the Finnish forest industry policy, as in the last decades the trend has been just the opposite. This shift would imply that the export revenues from the forest sector decline and, hence, that welfare declines, ceteris paribus. The proper analyses of welfare issues would take into account the reduction in pollution due ta the recycling but these issues are not dealt with in this paper. 1n addition we showed that if different types of paper face differing recycling requirements then we would expect a large structural change in paper production. We may see the cessation of production of the types of paper facing the highest recycling requirements, though this result depends on assumptions regarding relative capital intensities of production. If they do not differ between production processes of various types of paper then it certainly holds.
URN:NBN:fi:bof-201908121382
Keywords: 330